The Practicum subject in the initial formation of teachers in the new Degrees in Infant and Primary Education Training. The point of view of both tutors and students - González Garzón, Mª Leonor; Laorden Gutiérrez, Cristina (Pulso. Revista de educación, 2012)
In this article, we intend to present the experience developed with the subject Practicum I in the EUCC in the face of the new Degrees in Teacher Training: Infant Education and Primary Education. There is a twofold purpose: on the one hand, to show the formative model carried out and, on the other hand, to collect the opinions of both students and tutors involved in it. This model allows our students to bring closer to the school reality and allows us to introduce them into their first training period at schools. This model is based on the importance and the need to keep alive a constant reflection on the students previous learning experiences and those which take place at schools in order that students make explicit their learning. This article also deals with some essential elements as self-assessment, the specific formation of tutors, or the students emotions. With respect to the opinions of both students and tutors, the results show a very positive appraisement, and data analysis allows us to know both the strengths of our model as well as those points which are susceptible to improvement; these ones also offer us the possibility to develop innovative programmes in this direction.